2023
DOI: 10.1371/journal.pone.0289984
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of thrips populations on Allium species around the world

Bettina Porta,
Ben Vosman,
Richard G. F. Visser
et al.

Abstract: Thrips are a serious pest in many crops. In onion cultivation, Thrips tabaci is the most important, but not the only thrips species causing damage. We investigated which thrips species affects onion and related species worldwide, how much genetic variation there is within T. tabaci populations, and how this evolves. Furthermore, we determined the reproductive mode and the correlation between the genetic and geographic distances. Thrips samples from infested onions or related species were obtained from 14 diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 54 publications
0
0
0
Order By: Relevance
“…These results are also consistent with those of molecular phylogeny, which indicate that geographical proximity cannot be used to measure molecular evolutionary patterns in mtCOI. Recent investigations in T. tabaci populations inhabiting on Alliums did not determine any correlations between the genetic and geographic distances ( Li et al, 2020 ; Porta et al, 2023 ). The haplotype networks showed that Group A comprised eight haplotypes, with 307_Himachal Pradesh and 303_Haryana as the most distant haplotypes.…”
Section: Discussionmentioning
confidence: 82%
See 4 more Smart Citations
“…These results are also consistent with those of molecular phylogeny, which indicate that geographical proximity cannot be used to measure molecular evolutionary patterns in mtCOI. Recent investigations in T. tabaci populations inhabiting on Alliums did not determine any correlations between the genetic and geographic distances ( Li et al, 2020 ; Porta et al, 2023 ). The haplotype networks showed that Group A comprised eight haplotypes, with 307_Himachal Pradesh and 303_Haryana as the most distant haplotypes.…”
Section: Discussionmentioning
confidence: 82%
“…Nucleotide sequences of mtCOI gene were used for population genetics analysis of onion thrips from eight regions in India. This helped characterise species diversity, geographical distribution of a species, and tracing the phylogeographic origin ( Lombaert et al, 2014 ; Porta et al, 2023 ). In contemporary literature, only 28 haplotypes of mtCOI gene of T. tabaci have been reported worldwide, including Asia, Europe, Australia, America and other 23 countries, and these haplotypes were retrieved from nearly 282 nucleotide sequences ( Iftikhar et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations